1994
DOI: 10.1093/carcin/15.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Localization of oxidative damage by a glutathione-γ-glutamyl transpeptidase system in preneoplastic lesions in sections of livers from carcinogen-treated rats

Abstract: Previous studies from our laboratories have shown that catabolism of glutathione (GSH) by gamma-glutamyl transpeptidase (GGT) in the presence of transition metals leads to oxidative damage (OD). This damage is exemplified in vitro by GGT-dependent GSH mutagenesis which involves reactive oxygen species and by GGT-dependent accumulation of lipid peroxidation (LPO) products in systems containing polyunsaturated fatty acid and GSH. In order to test whether catabolism of GSH by membranal GGT in enzyme-altered prene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 0 publications
2
42
1
1
Order By: Relevance
“…Alternatively, we are interested in the possibility that body iron storage plays a role in this interaction between GGT and age, because the cellular role of GGT differs depending on iron storage. [8][9][10][11] In this study, among young subjects who probably had low body iron storage, 18 GGT showed no relationship with hypertension, whereas among old age subjects who probably had high body iron storage, 18 GGT was a strong risk factor for hypertension.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Alternatively, we are interested in the possibility that body iron storage plays a role in this interaction between GGT and age, because the cellular role of GGT differs depending on iron storage. [8][9][10][11] In this study, among young subjects who probably had low body iron storage, 18 GGT showed no relationship with hypertension, whereas among old age subjects who probably had high body iron storage, 18 GGT was a strong risk factor for hypertension.…”
Section: Discussioncontrasting
confidence: 49%
“…GGT is a key enzyme for transport of glutathione into cells. Furthermore, recent experimental studies [8][9][10][11] indicated that under physiological conditions, especially in the presence of iron, GGT is involved directly in reactive oxygen species generation as a pro-oxidant. Thus, it may be that GGT plays an antioxidant or pro-oxidant role, depending on the presence of iron or similar oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, serum GGT might increase with increasing exposure to xenobiotics which need to be conjugated to GSH. 24,25 In an experiment with carcinogen-treated rats, Stark and coworkers 42 found that metabolism of GSH by GGT in preneoplastic liver foci can initiate an oxidative process leading to a radical-rich environment and to oxidative damage. Such damage may contribute to the processes by which cells within such foci progress to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cysteinylglycine, which is one of the products of GGT action, has a strong ability to reduce Fe 3þ to Fe 2þ , which again promotes generation of free radical species. A GGT-mediated oxidative stress has been repeatedly reported, capable of inducing oxidation of lipids, [7,8] oxidation of protein thiols, [10] alterations of the normal protein phosphorylation patterns, [11] and biological effects such as the activation of transcription factors. [12,13] …”
Section: Cellular Gamma Glutamyltransferase (Ggt) and Oxidative Stresmentioning
confidence: 99%